1987
DOI: 10.1161/01.str.18.2.373
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol and dextran combined in the therapy of acute stroke. A placebo-controlled, double-blind trial with a planned interim analysis.

Abstract: The results of clinical trials investigating various therapies in acute ischemic stroke have been inconsistent. The effect of glycerol therapy and a combination therapy of glycerol and dextran was evaluated in a double-blind, placebo-controlled study. Repeated neurologic examinations (Day 0, Weeks 1, 6, 12, and 24) according to a modified Mathew score were performed on 62 patients. Statistical analysis showed no superiority of either treatment compared with placebo in acute ischemic stroke. A retrospective est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…26 Japanese clinicians have infused such mixtures into patients very rapidly, apparently without ill effect. 27 Following our preliminary experience, special care was taken to avoid excessive infusion rates; it was gratifying that after 7 days, the mean reduction of hemoglobin concentration in patients receiving glycerol in our study was much smaller (about Vi) than that reported by Frei et al 25 Indeed, following 6 days of glycerol or placebo treatment, mean reductions encountered in our patients were 0.54 and 0.12 g/dl, respectively; the difference of only 0.4 g/dl was statistically but not clinically significant (Table 5). Furthermore, such subclinical reductions in hemoglobin concentration after infusion of glycerol in saline may be attributed to a While our overall results show no clinically or statistically significant difference in outcome between patients treated with glycerol or saline, there were too few comatose and semicomatose patients to make any kind of reliable independent estimate of the effect of treatment within these strata.…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…26 Japanese clinicians have infused such mixtures into patients very rapidly, apparently without ill effect. 27 Following our preliminary experience, special care was taken to avoid excessive infusion rates; it was gratifying that after 7 days, the mean reduction of hemoglobin concentration in patients receiving glycerol in our study was much smaller (about Vi) than that reported by Frei et al 25 Indeed, following 6 days of glycerol or placebo treatment, mean reductions encountered in our patients were 0.54 and 0.12 g/dl, respectively; the difference of only 0.4 g/dl was statistically but not clinically significant (Table 5). Furthermore, such subclinical reductions in hemoglobin concentration after infusion of glycerol in saline may be attributed to a While our overall results show no clinically or statistically significant difference in outcome between patients treated with glycerol or saline, there were too few comatose and semicomatose patients to make any kind of reliable independent estimate of the effect of treatment within these strata.…”
Section: Resultssupporting
confidence: 47%
“…16 Discussion Hitherto, studies purporting to evaluate the possible beneficial effect of intravenous glycerol in patients with acute stroke have yielded contradictory and inconclusive results. 17 " 25 Commonly, there was no attempt to distinguish hemorrhagic from ischemic episodes (especially in earlier trials), and if attempted, objective confirmation of the diagnosis with CT was lacking or inconsistent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary mixed glial cells were prepared from 1 -3-day-old postnatal Sprague-Dawley rat pups, as described previously (33). Briefly, the brain cortices were pretreated in 0.25% trypsin solution containing of 1 mM EDTA and 1% papain for 5 min in a 37°C incubator, passed through a nylon mesh (100 μm), and plated at 2 × 10 5 cells /cm 2 in 0.01% poly-D-lysine-coated T-75 flasks.…”
Section: Cell Culturesmentioning
confidence: 99%
“…With the large doses of steroids which have been used, infective complications and elevation of plasma glucose or exacerbation of diabetes are frequent (Poungvarin et al, 1987). Despite many studies with intravenous glycerol there is no consensus on its effect on stroke (Bayer et al, 1987;Fawer et al, 1978;Frei et al, 1987;Gilsanz et al, 1975;Larsson et al, 1976;Mathew et al, 1972;Meyer et al, 1975). In an overview of the published trials, Sandercock (1987) concluded that the 6 week mortality in stroke patients after glycerol may fall by 36% compared with placebo, but that the 95% confidence limits for this improvement range from 4%-58%.…”
Section: Anti-oedema and Other Agentsmentioning
confidence: 99%